2014
DOI: 10.1002/jcb.24737
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Modulates Proliferation and Mitochondrial Functionality in Breast Cancer Cells Depending on ERalpha/ERbeta Ratio

Abstract: Breast cancer is the most common malignancy in women of developed countries. The aim of this study was to investigate whether genistein, a soy phytoestrogen, and 17β-estradiol (E2) could have effects on the cell cycle and mitochondrial function and dynamics. Three human breast cancer cell lines with different estrogen receptor alpha (ERα) and estrogen receptor beta (ERβ) ratio were used: MCF-7 (high ERα/ERβ ratio), T47D (low ERα/ERβ ratio) and MDA-MB-231 (ER-negative). Cell proliferation, cell cycle, mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 45 publications
2
59
3
Order By: Relevance
“…Previous results obtained in our laboratory demonstrated the importance of the ER␣/ER␤ ratio in the maintenance of mitochondrial redox homeostasis (Nadal-Serrano et al, 2013;Pons et al, 2014;Sastre-Serra et al, 2013a;2012b). Thus, exposure to cells with a high ER␣/ER␤ ratio to 17␤-estradiol (E2) or genistein (GEN), a phytoestrogen capable to bind both ERs, provoked an increase in ROS production and a loss of mitochondrial functionality.…”
Section: Introductionmentioning
confidence: 85%
“…Previous results obtained in our laboratory demonstrated the importance of the ER␣/ER␤ ratio in the maintenance of mitochondrial redox homeostasis (Nadal-Serrano et al, 2013;Pons et al, 2014;Sastre-Serra et al, 2013a;2012b). Thus, exposure to cells with a high ER␣/ER␤ ratio to 17␤-estradiol (E2) or genistein (GEN), a phytoestrogen capable to bind both ERs, provoked an increase in ROS production and a loss of mitochondrial functionality.…”
Section: Introductionmentioning
confidence: 85%
“…Genistein also has extensive pharmacological effects in animal cells. A previous study found that genistein has anticancer effects, including in vitro antitumor effects in human breast cancer cell lines (12) and prostate cancer cells (13). Thus, genistein is a potential cancer chemoprevention agent with a broad development prospect (14).…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that calycosin and genistein inhibit many types of cancers including breast cancer [4,5,6,7] through the regulation of several cell signaling pathways such as the mitogen-activated protein kinases (MAPK), Akt and JAK/STAT pathways [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%